PLURALISM AS A RECOMMENDED RESEARCH PRACTICE FOR CENTRAL BANKS IN ADDRESSING WELFARE CONCERNS ON THE EXPERIENCE OF COVID-19 - JACKSON, Emerson Abraham (Theoretical and Practical Research in Economic Fields; Vol 12 No 1 (2021): TPREF, Volume XII, Issue 1(23), Summer 2021, 2021)
The theoretical discourse of pluralism in this paper has paved the way for central banks research approach to accommodate variety in methodological application, which currently seem to be skewed in the direction of monism. In the interest of ensuring welfare concern for citizens is addressed in the best possible way, this paper has expanded its discourse to incorporate economic pluralism that favours variety of methods. This notably include qualitative and quantitative approaches, with the emphasis of digressing on the new entrant of Mixed Research Synthesis (MRS). Such an approach will seek to explore research capacity in support of addressing opportunities for decent citizens’ welfare as the impact of COVID-19 unfold itself.